Arthroscopic Guided Synovial Biopsies - Orr, Carl Kieran; Vieira-Sousa, Elsa; Fonseca, João Eurico; Veale, Douglas (Frontiers in Medicine, 2021)
The synovium is the primary target tissue in inflammatory arthritis (IA), and it therefore follows that analysis of this tissue must yield important clues to advance our understanding of the underlying pathobiology of these heterogenous diseases. The field has rapidly expanded over the last three decades, and this has led to some very significant developments in unravelling the cellular and molecular networks underlying the development and perpetuation of IA1–4. Putative targets have been identified by synovial tissue (ST) analysis5. ST has been used in the evaluation of current and potential treatments, in both in vivo and ex vivo settings6,7. Recent evidence suggests that it may be possible to stratify patients with rheumatoid arthritis (RA) on the basis of histopathology and transcriptomic analysis, into groups with differing underlying pathobiology, and with differential responses to therapies8–10. These developments rely on safe retrieval of synovial tissue. Although much data has been published on tissue retrieved at arthroplasty, the suitability and applicability of these findings to IA at much earlier timepoints in the disease course remains unclear. Therefore, arthroscopy was adopted by Rheumatologists to allow ST sampling at varying points in the disease course and has long been the favoured technique historically. This technique has the advantage of providing direct intra-articular visualization of synovium as well as a therapeutic joint lavage. In this review, we describe the general aspects of the technique of arthroscopic guided synovial biopsies (AGSB) of the knee joint under local anaesthetic, as performed in two European Rheumatology Centres.